2003
DOI: 10.3171/jns.2003.98.4.0737
|View full text |Cite
|
Sign up to set email alerts
|

The use of recombinant activated factor VII to reverse warfarin-induced anticoagulation in patients with hemorrhages in the central nervous system: preliminary findings

Abstract: This clinical experience indicates that rFVIIa may be safe and effective as the initial hemostatic agent for rapid reversal of orally administered anticoagulation medications in patients who require urgent neurosurgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(70 citation statements)
references
References 22 publications
1
67
0
2
Order By: Relevance
“…However, FVIIa also increases the plasma activities of factors IX and X in a dose-dependent manner (20). Observations of our patients and several previously published case series have demonstrated the efficacy of FVIIa in normalizing the INR as well as in stopping bleeding in a variety of clinical situations, including bleeding associated with excessive anticoagulation (9,(11)(12)(13). Therefore, we believe that correction of the abnormal INR is likely to be associated with a correction of the in vivo coagulopathy as well.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, FVIIa also increases the plasma activities of factors IX and X in a dose-dependent manner (20). Observations of our patients and several previously published case series have demonstrated the efficacy of FVIIa in normalizing the INR as well as in stopping bleeding in a variety of clinical situations, including bleeding associated with excessive anticoagulation (9,(11)(12)(13). Therefore, we believe that correction of the abnormal INR is likely to be associated with a correction of the in vivo coagulopathy as well.…”
Section: Discussionmentioning
confidence: 81%
“…Activated FVII has recently been used to correct bleeding diatheses in several scenarios, including warfarin-associated intracranial and intraspinal hematomas (11)(12)(13). It acts by directly binding to tissue factor to activate thrombin generation, bypassing much of the cascade of coagulation factors (14).…”
Section: Discussionmentioning
confidence: 99%
“…53 Small numbers of patients with ICH successfully treated with rFVIIa have been reported recently. [54][55][56] On the basis of this limited data, the role of rFVIIa in warfarin reversal remains unclear. Further studies are required to establish the optimum dose and confirm safety.…”
Section: Is There a Role For Rfviia In Rapid Warfarin Reversal?mentioning
confidence: 99%
“…74,75 Early reports of the off-label use of rFVIIa from one of our institutions as well as others on the successful management of warfarinassociated ICH with rFVIIa therapy led to the development of single-institution policies for oversight of its off-label use. [76][77][78][79][80] The value of rFVIIa in patients with spontaneous ICH who were not on warfarin anticoagulation underwent scrutiny in clinical trials in which it was shown to reduce growth of hematoma if administered within 4 hours of onset, 81 but it did not improve survival or functional outcome. 82 A subsequent post hoc analysis of these trials suggested that the use of rFVIIa was most beneficial and associated with improved outcomes in patients Յ 70 years old who had lower baseline hemorrhage volume and shorter time from onset to treatment.…”
Section: Prothrombin Complex Concentratesmentioning
confidence: 99%